Early brain imaging predictors of post-stroke spasticity - Songjin Ri; Stefanie Glaess-Leistner; Jörg Wissel (Medical Journals Sweden, 2021)
Background: Post-stroke spasticity is a major factor disturbing rehabilitation and functional recovery in stroke survivors. Clinical predictors of post-stroke spasticity have often been discussed, but brain image predictors for spasticity have been insufficiently researched. The aim of this study was to use magnetic resonance imaging data to identify early brain imaging predictors for potential development of spasticity after stroke. Methods: Consecutive patients admitted to a stroke unit were screened prospectively over 22 months. Patients with first-ever supratentorial ischaemic stroke were included in the study. Standardized clinical assessments for post-stroke spasticity were prospectively performed within 7 days and at 3 months. Brain imaging data (3 Tesla magnetic resonance imaging (3T MRI)) were collected at the baseline and evaluated. Results: Brain imaging data from 103 stroke patients were collected in the hyperacute phase (< 7 days after stroke onset). A total of 23 patients developed post-stroke spasticity. The volumes of brain lesions involving motor network areas were significantly larger in patients with post-stroke spasticity compared with those without post-stroke spasticity (p < 0.01). Supratentorial lesion of < 0.5 cm3 were not associated with risk of post-stroke spasticity, except when the internal capsule and striatum was affected. Conclusion: Lesions involving motor network areas are considered to be a precondition of post-stroke spasticity. There is, however, a low risk of developing post-stroke spasticity with < 0.5 cm3 volumes of supratentorial brain lesions involving motor network areas. Larger volume brain lesions involving motor network areas, e.g. > 3 cm3, were significantly more common in patients with post-stroke spasticity. Pure cortical lesions has no risk of post-stroke spasticity in stroke survivors.